An ionic gel thin film, a preparation method thereof and an ionic thin film pressure sensor

CN122917467APending Publication Date: 2026-10-16WUTONG SENSATION CONTROL (BEIJING) TECH CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611400359.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]本发明的主要目的在于提供一种离子凝胶薄膜及其制备方法和离电型薄膜压力传感器,旨在解决现有的离子凝胶薄膜回弹性较差、力学响应延迟的问题,以及离电型薄膜压力传感器电学信号延迟导、精准性能较低、系统稳定性较差的问题

Benefits of technology

[0016] Compared with the prior art, the beneficial effects that the present invention can achieve are as follows.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917467A_ABST
    Figure CN122917467A_ABST
Patent Text Reader

Abstract

The application discloses an ionic gel thin film, a preparation method thereof and an ionic thin film pressure sensor, and belongs to the technical field of flexible pressure sensors. By selecting a PVDF with a weight average molecular weight of 0.9-1.1 million g / mol and a molecular weight distribution of 2.5-3.0 and a PVDF-HFP compound with a weight average molecular weight of 0.4-0.6 million g / mol and a molecular weight distribution of 1.5-2.0, a three-dimensional skeleton network structure with a double-network and double-relaxation mechanism and a multi-stage and multi-porous connected structure are constructed in the ionic gel thin film, so that technical effects such as high resilience, fast response and synchronous response are realized, and the problems of poor resilience and delayed mechanical response of the existing ionic gel thin film are solved. The ionic thin film pressure sensor containing the ionic gel thin film has the ability of synchronous conversion of mechanical signals and electrical signals, so that the problem of delayed electrical signals of the sensor is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of flexible pressure sensor technology, and in particular to an ion gel film, its preparation method, and an ionized film pressure sensor. Background Technology

[0002] Flexible pressure sensors are widely used in flexible electronic skin, wearable medical devices, and human-computer interaction. Ionized thin-film pressure sensors are a new type of flexible pressure sensor based on the triboelectric effect and electrostatic induction principle. Ion gel films are their core pressure-sensitive functional layers, essentially solid or quasi-solid gel materials formed by fixing ionic liquids through a polymer network. In the working mechanism of ionized thin-film pressure sensors, the core principle of the ion gel as the pressure-sensitive layer is based on the interfacial double-layer capacitance effect. When the ion gel comes into contact with the paired triboelectric layer, charge transfer occurs at the interface; positive and negative ions in the ionic liquid separate and arrange at the interface, forming a nanoscale double layer; pressure changes the effective contact area and the thickness of the double layer, thus significantly changing the interfacial capacitance; accompanied by the contact-separation mechanical motion, measurable voltage and current signals are generated.

[0003] Existing methods for preparing ionogel films generally involve dissolving polar polymers and electrolytes in a good solvent, followed by solvent evaporation. However, in this method, due to the lack of a three-dimensional structure in the polar polymers, the interactions between polymer chains are weak during deformation and recovery, resulting in lag in deformation recovery and poor resilience in the resulting ionogel films. Alternatively, ion liquids can be pre-dispersed in polymer monomers and prepolymers, and then the ion liquids are bound within the polymer network during monomer polymerization and cross-linking. However, this method requires high compatibility between the polymer monomers and prepolymers due to the high polarity of the ion liquids, typically necessitating the use of multiple polymer blends to achieve the desired results.

[0004] Furthermore, after decompression, the molecular chain segment movement and rearrangement of the ionogel film substrate require time, resulting in a delayed mechanical response, which manifests as a delay in the sensor's electrical signal. Simultaneously, the plasticizing effect of the ionic liquid on the substrate further exacerbates this electrical signal delay. This delay in electrical signal leads to decreased sensor accuracy and reduced system stability, thus limiting the sensor's application scenarios. Summary of the Invention

[0005] The main objective of this invention is to provide an ion gel film, its preparation method, and an ionized film pressure sensor, aiming to solve the problems of poor resilience and delayed mechanical response of existing ion gel films, as well as the problems of delayed electrical signals, low accuracy, and poor system stability of ionized film pressure sensors.

[0006] To achieve the above objectives, the present invention provides an ion gel film, the ion gel film comprising a three-dimensional framework network structure and a multi-level porous interconnected structure; The ion gel film system includes a PVDF / PVDF-HFP composite; In the PVDF / PVDF-HFP compound, the weight-average molecular weight of PVDF is 900,000-1,100,000 g / mol, and the molecular weight distribution is 2.5-3.0; the weight-average molecular weight of PVDF-HFP is 400,000-600,000 g / mol, and the molecular weight distribution is 1.5-2.0.

[0007] Optionally, the ionogel film system further includes a crosslinking system; the crosslinking system accounts for 5-15 parts of the ionogel film system by mass. The crosslinking system comprises, by mass percentage, 60-83% methacrylate compound, 15-30% crosslinking agent, and 5-10% initiator; The methacrylate compound is composed of at least two of the following: methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, and isobutyl methacrylate. The PVDF / PVDF-HFP composite accounts for 5-20 parts by mass of the ionogel film system; In PVDF / PVDF-HFP blends, by mass percentage, PVDF is 60-95% and PVDF-HFP is 5-40%.

[0008] Optionally, the ionogel film system may further include 3-10 parts of ionic liquid, 0.1-2.0 parts of nanofiller, and 60-85 parts of compound solvent by mass.

[0009] Optionally, the crosslinking agent includes at least one of trimethylolpropane triacrylate, triallyl isocyanurate, polyethylene glycol diacrylate, ethylene glycol dimethacrylate, and dicumyl peroxide; The initiator includes at least one of azobisisobutyronitrile, 1,1'-azobiscyclohexanenitrile, and benzoyl peroxide.

[0010] Optionally, the ionic liquid comprises at least one of 1-ethyl-3-methylimidazolium trifluoromethanesulfonylimide, 1-butyl-3-methylimidazolium di(trifluoromethanesulfonyl)imide, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium hexafluorophosphate, 3-methyl-1-hexylimidazolium bromide, and 1-ethyl-3-methylimidazolium acetate; The nanofiller includes at least one of nano zinc oxide, nano aluminum oxide and nano silicon nitride; The compounded solvent comprises, by mass percentage, 60-85% of a first solvent, 10-30% of a second solvent, and 5-15% of a third solvent.

[0011] Optionally, the first solvent includes N,N-dimethylformamide or N,N-dimethylacetamide; the second solvent includes N-methylpyrrolidone; and the third solvent includes dimethyl carbonate.

[0012] To achieve the above objectives, the present invention also provides a method for preparing an ion gel film, the method being used to prepare an ion gel film as described above; The preparation method includes: The PVDF / PVDF-HFP composite was dissolved in a compounding solvent and stirred at room temperature until the solution was uniform and transparent. Then, ionic liquid and nanofiller were added sequentially, and after ultrasonic treatment, the solution was allowed to stand at room temperature to obtain an ion gel-based solution. A crosslinking system was added to the ion gel-based solution and stirred at room temperature until homogeneous to obtain the ion gel film system. Using a coating equipment and based on a coating process, the ionogel film system is coated onto the surface of a backing substrate to form a wet film coating. Then, the film undergoes a first drying process and a second drying process to obtain the ionogel film attached to the surface of the backing substrate.

[0013] Optionally, the steps of sequentially performing a first drying process and a second drying process include: After the ionogel film system is coated on the surface of the backing substrate, it is placed in a drying equipment and dried at 70-85℃ for 3-24 hours; then it is vacuum dried at 70-80℃ for 48-72 hours using a vacuum drying equipment.

[0014] Optionally, the thickness of the wet film coating is 100-2000 μm.

[0015] To achieve the above objectives, the present invention also provides an ionized thin-film pressure sensor, which includes the ionized gel thin film as described above.

[0016] Compared with the prior art, the beneficial effects that the present invention can achieve are as follows.

[0017] 1. In the ionogel film disclosed in this invention, PVDF with a weight-average molecular weight of 900,000-1,100,000 g / mol and a molecular weight distribution of 2.5-3.0 is selected as the elastic framework. When the material is stretched or compressed by external force, the chain segments of this elastic framework undergo orientation changes and store entropy elastic potential energy. When the external force is removed, it provides a restoring force, enabling the material to return to its original shape and possess high resilience and low hysteresis performance. PVDF-HFP has a weight-average molecular weight of 400,000-600,000 g / mol and a molecular weight distribution of 1.5-2.0. The molecular chains are relatively short, the chain segments have strong mobility, and the relaxation time is short. Under the action of external force, these chain segments can adjust their conformation more quickly, realizing rapid stress transmission. Moreover, the introduction of HFP can increase the proportion of amorphous regions, enabling PVDF-HFP to absorb more ionic liquids and form continuous ion transport channels. By combining PVDF and PVDF-HFP, the resulting PVDF / PVDF-HFP composite can construct a three-dimensional framework network structure with dual networks and dual relaxation mechanisms, as well as a multi-level porous interconnected structure in ion gel films. This achieves technical effects such as high resilience, fast response, and synchronous response, solving the problems of poor resilience and delayed mechanical response in existing ion gel films.

[0018] 2. The method for preparing ion gel films with high resilience and low hysteresis disclosed in this invention complements the ion gel films, enabling the resulting ion gel films to possess characteristics such as rapid response and high resilience. When applied to ionized thin-film pressure sensors, the synergistic and complementary molecular and structural features of PVDF-HFP and PVDF allow for almost synchronous conversion between mechanical and electrical signals, thereby solving the problems of sensor electrical signal delay, decreased accuracy, and poor system stability. Attached Figure Description

[0019] Figure 1 This is a schematic diagram of the structure of the ionized thin-film pressure sensor in the embodiment; Figure 2 The image shows the FTIR characterization of the ionogel film of Example 1. Figure 3 This is a SEM image of the ionogel film from Example 1; Figure 4 The graph shows the dynamic response characteristics of the ionized thin-film pressure sensor containing the ionized gel film of Example 1. Figure 5 This is a test graph showing the long-term stability of an ionized thin-film pressure sensor containing the ion gel film of Example 1. Detailed Implementation

[0020] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. It should be noted that, unless otherwise specified, the following substances can be prepared by known methods or commercially available; in the process of substance preparation, unless otherwise specified, the reaction involving crosslinking agents, functional additives, temperature, and other reaction conditions are all considered to be known technical implementations. If not explicitly given in the text, it does not mean that the substances of this application cannot be obtained.

[0021] To address the issues of poor resilience and delayed mechanical response in existing ion gel films, as well as the decreased accuracy and system stability caused by the delay in electrical signals from ionized thin-film pressure sensors, this invention provides an ion gel film comprising a three-dimensional skeletal network structure and a multi-level porous interconnected structure. The components of the ionogel film include a PVDF / PVDF-HFP composite. In PVDF / PVDF-HPF complexes, the weight-average molecular weight of PVDF is 900,000-1,100,000 g / mol, and the molecular weight distribution is 2.5-3.0; the weight-average molecular weight of PVDF-HFP is 400,000-600,000 g / mol, and the molecular weight distribution is 1.5-2.0.

[0022] It should be understood that the weight-average molecular weight (Mw) of the aforementioned PVDF (polyvinylidene fluoride homopolymer) is 900,000-1,100,000 g / mol. Weight-average molecular weight refers to the average molecular weight weighted by molecular weight, reflecting the average weight-level of the polymer chain. 900,000-1,100,000 g / mol represents ultra-high molecular weight PVDF. Molecular weight distribution ( The Mw / Mn ratio is 2.5-3.0, and the molecular weight distribution index (Mw / Mn) is 2.5-3.0. = Weight-average molecular weight / Number-average molecular weight = Mw / Mn, 2.5-3.0 is a relatively broad distribution. The weight-average molecular weight of the above PVDF-HFP (polyvinylidene fluoride-hexafluoropropylene copolymer) is 400,000-600,000 g / mol, which is in the medium to high range, and the molecular weight distribution is 1.5-2.0, which is a relatively narrow distribution (the closer the value is to 1, the closer the length of all molecular chains are, and the more homogeneous the system is).

[0023] Optionally, the PVDF and PVDF-HFP mentioned above can be commercially available finished products, or they can be synthesized according to actual needs, and no specific limitations are made here.

[0024] Optionally, in specific embodiments of the technical solution disclosed in this invention, under the premise that the weight-average molecular weight of PVDF is 900,000-1,100,000 g / mol and the molecular weight distribution is 2.5-3.0; and the weight-average molecular weight of PVDF-HFP is 400,000-600,000 g / mol and the molecular weight distribution is 1.5-2.0, the weight-average molecular weight and the molecular weight distribution of the interval can be selected, or specific values ​​of weight-average molecular weight and specific values ​​of molecular weight distribution can be selected.

[0025] It should be understood that, according to existing research data, the weight-average molecular weight and molecular weight distribution of PVDF and PVDF-HFP can be controlled by the preparation process of PVDF and PVDF-HFP, for example, by adjusting process parameters such as polymerization temperature, initiator concentration, chain transfer agent, pressure and monomer concentration.

[0026] It should be noted that in ionogel films, after plasticization by ionic liquids, the polymer chains become excessively relaxed and difficult to return to their original state after deformation, resulting in poor resilience. In addition, the relaxation time of chain segment movement is relatively long, and there is a hysteresis phenomenon in stress transmission. At the same time, the viscous resistance of ionic liquids also slows down the response speed, which leads to a delay in mechanical response.

[0027] In the aforementioned ionogel films with high resilience and low hysteresis, the PVDF selected is a PVDF with a weight-average molecular weight of 900,000-1,100,000 g / mol and a molecular weight distribution of 2.5-3.0. This PVDF is an ultra-high molecular weight, wide-distribution PVDF, which forms the elastic framework in the gel film. The weight-average molecular weight of 900,000-1,100,000 g / mol indicates that the molecular chains in the PVDF are relatively long, enabling the formation of a dense physical entanglement network in the system. This entanglement network has a spring-like capability; when the material is stretched or compressed by external forces, the chain segments undergo orientation changes, storing entropic elastic potential energy. When the external force is removed, this entanglement network provides a restoring force, driving the material back to its original shape. When the molecular weight distribution is 2.5-3.0, it indicates that both long and short chains exist in the PVDF system. The long chains can form an entangled network, providing overall mechanical strength and creep resistance; the short chains can fill the gaps between the long chains, acting as a stress transfer medium. When external force is applied to the material, the short chains can quickly disperse the stress into the overall structure of the network, avoiding permanent deformation caused by local stress concentration. Furthermore, chains of different lengths have different relaxation times. This multi-scale relaxation capability can cover a wider frequency range, allowing the material to exhibit good response characteristics at different deformation rates.

[0028] The aforementioned PVDF-HFP uses PVDF-HFP with a weight-average molecular weight of 400,000-600,000 g / mol and a molecular weight distribution of 1.5-2.0, possessing the ability to form a fast-response channel. Specifically, when the weight-average molecular weight is 400,000-600,000 g / mol, the molecular chains are relatively short, resulting in strong chain segment mobility and short relaxation times. Under external forces, these chain segments can adjust their conformation more quickly, achieving rapid stress transfer. When the molecular weight distribution is 1.5-2.0, the molecular weight distribution is narrower, and the chain length in the system is more uniform, with some chain segments having similar relaxation times. This uniformity avoids the problem of dispersed relaxation times caused by excessive differences in chain length, preventing the phenomenon where some chain segments have already responded while others are still slowly adjusting. Simultaneously, the introduction of HFP increases the proportion of amorphous regions, enabling PVDF-HFP to absorb more ionic liquids, forming continuous ion transport channels. The molecular weight distribution range ensures that it does not excessively swell or soften, thus preventing loss of shape stability.

[0029] Furthermore, through the above-mentioned PVDF and PVDF-HFP compounding, the PVDF / PVDF-HFP composite can construct a three-dimensional framework network structure with a dual-network and dual-relaxation mechanism, and a multi-level porous interconnected structure in ion gel films. In this structure, the high molecular weight long chains of PVDF can form a physically entangled network framework, which has the ability to store elastic potential energy and resist permanent deformation. After the material is compressed, the network framework can provide the driving force for rebound. Meanwhile, the medium molecular weight segments of PVDF-HFP can fill the gaps in the network framework, forming highly fluid regions, which allow stress to be quickly transmitted through these regions. At the same time, the ionic liquid can form a transport channel with low viscous resistance in these regions. In terms of phase structure morphology analysis, PVDF, due to its high crystallinity tendency, easily forms a hard segment phase rich in crystalline regions in the film; while PVDF-HFP tends to form a soft segment phase rich in ionic liquids. This microphase separation structure of hard and soft segments allows for the formation of an alternating distribution of hard and soft regions within the system. When external forces are applied, the hard regions rapidly transmit stress, and the soft regions quickly adapt to deformation. The two work together to ensure both response speed and avoid permanent deformation of purely soft materials.

[0030] Therefore, in the technical solution of this invention, the PVDF / PVDF-HFP composite in the ionogel film achieves high resilience, rapid response, and synchronous response through design from the dimensions of weight-average molecular weight and molecular weight distribution. Through design from the dimension of swelling behavior, the low swelling characteristics of PVDF allow it to maintain skeletal rigidity after absorbing ionic liquids, ensuring rapid rebound after deformation. The high swelling characteristics of PVDF-HFP absorb a large amount of ionic liquid, providing efficient ion conduction channels, while the control of molecular weight prevents excessive softening. Finally, through the synergistic design of these three dimensions, elastic recovery, rapid response compatibility, and balance are achieved, solving the problems of poor resilience and delayed mechanical response in existing ionogel films, resulting in an ionogel film with high resilience and low hysteresis.

[0031] In one possible implementation, the above-described ionogel film system further includes a crosslinking system; the crosslinking system accounts for 5-15 parts by mass of the ionogel film system. The crosslinking system comprises, by mass percentage, 60-83% methacrylate compound, 15-30% crosslinking agent, and 5-10% initiator; The above-mentioned methacrylate compound is composed of at least two of the following: methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, and isobutyl methacrylate. The above PVDF / PVDF-HFP composite accounts for 5-20 parts by mass of the ionogel film system; In the above PVDF / PVDF-HFP compound, by mass percentage, PVDF is 60-95% and PVDF-HFP is 5-40%.

[0032] It should be understood that the aforementioned methyl methacrylate (MMA), ethyl methacrylate (EMA), propyl methacrylate (PrMA), n-butyl methacrylate (n-BMA), and isobutyl methacrylate (i-BMA) all contain polymerizable carbon-carbon double bonds, enabling them to undergo free radical polymerization via thermal initiation, photoinitiation, or radiation initiation to form a chemically cross-linked network. The length of the ester side chains is adjustable, allowing for precise control of the material's hydrophobicity, glass transition temperature, and chain segment mobility. After compounding (polymerization), the resulting polymethacrylate exhibits excellent performance in terms of optical transparency and good compatibility with ionic liquids.

[0033] Optionally, when selecting MMA, EMA, PrMA, n-BMA, and i-BMA from the above-mentioned methacrylate complexes, the selection can be made according to the actual application needs of the sensor, or according to the optional methods described below. In addition, when performing the complexation in a specific application, when selecting short-side-chain monomers MMA, EMA, and i-BMA and long-side-chain monomers n-BMA and PrMA for complexation, the complexation principle can follow the principle that the proportion of short-side-chain monomers is greater than or equal to that of long-side-chain monomers.

[0034] Optionally, when MMA and n-BMA are compounded, the compounding ratio can be 6:4-7:3. In this compound, MMA provides high Tg hard segments, which form glassy microdomains after polymerization, serving as physical crosslinking anchors to prevent plasticizing softening by ionic liquids and ensuring that the film still has sufficient modulus after swelling. n-BMA provides low Tg soft segments, and the straight-chain butyl groups impart high mobility to the segments, which are in a highly elastic state at room temperature, forming flexible channels for ion transport. In addition, when the straight-chain side chains of n-BMA are stretched or compressed, they tend to align, resulting in strain-induced crystallization and local ordering. This ordering is accompanied by additional stress response (strain hardening), which allows the sensor to maintain a monotonic response over a wide pressure range and is less prone to saturation. Furthermore, the physical entanglement network of PVDF can store entropic elastic energy during deformation, while the hard segment microdomains formed by MMA assist in energy storage through chemical bond deformation, and the soft segments of n-BMA can quickly transfer stress and adapt to deformation. The three work synergistically to form a multi-level structure with alternating soft and hard components.

[0035] Optionally, when EMA and i-BMA are blended, the ratio can be 5:5 to 6:4. EMA provides moderate modulus and response speed, while i-BMA increases ion migration rate. Furthermore, i-BMA prevents tight chain packing, maintaining the polymer's amorphous state and enhancing the absorption capacity of the ionic liquid, making phase separation or crystallization less likely after absorption. Further, the amorphous region in the PVDF-HFP structure may form a continuous, low-resistance ion channel with the high free volume region of i-BMA, while the moderate Tg region of EMA can act as a transition layer, buffering the modulus mismatch between the PVDF hard framework and the i-BMA soft region, reducing interfacial stress concentration. This blending method may be suitable for high-frequency dynamic sensing applications.

[0036] When using a ternary compounding scheme, MMA, EMA, and n-BMA can be selected and compounded in a ratio of 3:3:4. All three components are straight-chain alkyl esters, and copolymerization may result in a broad Tg distribution. At room temperature, some chain segments, such as the n-BMA-rich region, may be activated, while others, such as the MMA-rich region, may remain frozen, thus forming a soft-hard bicontinuous phase structure and enabling microphase separation. Furthermore, in systems combined with PVDF-HFP, a continuous modulus transition may occur, preventing abrupt interface changes in stress transfer. This scheme may be suitable for scenarios with stringent requirements for extreme temperature stability.

[0037] EMA, n-BMA, and i-BMA can be combined in a ratio of 5:3:2. EMA serves as the main component, ensuring sufficient shape stability at room temperature. n-BMA provides low Tg soft segments and high ion conductivity. The branched structure of i-BMA introduces high free volume, and its Tg is close to that of EMA, so it will not form a significant third phase. It can be uniformly dispersed in the EMA / n-BMA matrix, playing a role in molecular-level plasticization.

[0038] When using a quaternary composite system, MMA, EMA, n-BMA, and i-BMA can be blended in a ratio of 2:3:3:2. MMA provides hard segments, EMA serves as the main framework, n-BMA provides soft segments and ion channels, and i-BMA provides free volume and creep-resistant branching structures. This quaternary composite system can provide copolymers with a broad Tg distribution, simultaneously exhibiting glassy microregions, leathery transition regions, and a rubbery continuous phase at room temperature, forming a three-phase coexistence structure. This structure may possess the strain-reinforced crystallization mechanism of natural rubber, with the rubbery region dominating under low stress and the glassy region gradually activating and participating in load-bearing under high stress. Furthermore, the broad Tg distribution of PVDF and the broad Tg distribution of the methacrylate quaternary copolymer can form a dual-broad distribution match, enabling synergistic responses across multiple time scales and stress levels, potentially meeting full-spectrum sensing requirements from static pressure to high-frequency vibrations.

[0039] It should be understood that the total mass of the above crosslinking system can be taken as 100%, and the sum of the methacrylate compound, crosslinking agent, and initiator can be 100%.

[0040] It should be noted that in the above crosslinking system, the methacrylate compound is the main component. In the final chemical network, there may be 65-80 methacrylate monomers in every 100 structural units. This high proportion can ensure the continuity and integrity of the polymer backbone, so that the network has sufficient chain length and entanglement density, and can avoid fragmentation caused by excessive crosslinking agent. In the system, the crosslinking agent may construct a three-dimensional cage-like network. At high crosslinking densities, the average molecular weight between two crosslinking points may be compressed, causing the chain segments to lose their long-range slip capability. Thus, the resulting network structure exhibits strong resistance to swelling by ionic liquids. Even when absorbing large amounts of ionic liquid, the pore size of the network structure may still be limited by the chemical crosslinking points, preventing the gel from experiencing infinite swelling or strength collapse. Furthermore, high crosslinking density allows the material system to possess excellent entropy elastic recovery. When the external force is removed, the conformational entropy of the short-chain network segments has a strong driving force, enabling rapid deformation recovery and significantly reducing the mechanical hysteresis of the sensor. Simultaneously, this network structure possesses rigidity and may be more moduli-wise similar to the physically entangled network of PVDF. The two deform synergistically under stress, reducing interfacial slip and energy dissipation caused by modulus mismatch. The introduction of an initiator can overcome the diffusion difficulties of high-viscosity systems, reduce free radical interference from ionic liquids, and match the kinetics of high crosslinking densities.

[0041] In the above-mentioned PVDF / PVDF-HFP composites, when PVDF is 60-95% and PVDF-HFP is 5-40%, a three-level structural system can be constructed with ultra-high molecular weight physical entanglement as the framework, HFP amorphous regions as ion storage gaps, and methacrylate chemical crosslinking as the shape framework; and by adjusting the ratio, a wider process window may be provided for the range design of the sensor.

[0042] In one possible implementation, the above-mentioned ionogel film system further includes 3-10 parts of ionic liquid, 0.1-2.0 parts of nanofiller, and 60-85 parts of compound solvent by weight.

[0043] It should be understood that in the above-mentioned ionogel film system, there are 5-20 parts of PVDF / PVDF-HFP composite, 5-15 parts of crosslinking system, 3-10 parts of ionic liquid, 0.1-2.0 parts of nanofiller, and 60-85 parts of composite solvent. The total mass of each component is 100 parts. The actual proportions can be adjusted within the above range.

[0044] It should be noted that in the above-mentioned ionogel film system, the PVDF / PVDF-HFP composite is 5-20 parts. Within this range, not only can the film have basic skeletal support and film formation continuity be guaranteed, but it can also avoid the casting difficulties caused by excessively high solution viscosity, and prevent the polymer skeleton from being too dense, thus hindering the swelling and ion migration of the ionic liquid. If the mass fraction is less than 5 parts, the film may not be able to form a self-supporting film due to the low polymer concentration, or a large number of pinhole defects may appear. If it exceeds 20 parts, the solution viscosity will increase significantly, which is not conducive to the uniform coating of the gel. The crosslinking system is 5-15 parts. After the solvent of the gel film evaporates, a high-density chemical crosslinking network can be constructed in the dry film. Furthermore, the ratio of the crosslinking system to the PVDF / PVDF-HFP composite is between 0.4 and 1.5. When the ratio is >1, the chemical network may become dominant, and when the ratio is <1, the above-mentioned physical entanglement network structure may become dominant. A 3-10 part ionic liquid is sufficient to ensure continuous ion conduction channels, forming an effective double-layer capacitance, while avoiding problems such as film stickiness, excessive mechanical strength, and ionic liquid leakage caused by over-plasticization. 0.1-2.0 parts of nanofiller are at the level of trace functional additives, possessing surface modification, nucleation agent, mechanical reinforcement, thermal conductivity, and dielectric regulation functions; exceeding 2.0 parts may lead to agglomeration, which will disrupt film uniformity. 60-85 parts of compound solvent make the resulting ionogel system suitable for processes such as doctor blade coating, spin coating, and casting.

[0045] In one possible implementation, the crosslinking agent includes at least one of trimethylolpropane triacrylate, triallyl isocyanurate, polyethylene glycol diacrylate, ethylene glycol dimethacrylate, and dicumyl peroxide. The aforementioned initiators include at least one of azobisisobutyronitrile, 1,1'-azobiscyclohexanenitrile, and benzoyl peroxide.

[0046] In one possible embodiment, the above-mentioned ionic liquid includes at least one of 1-ethyl-3-methylimidazolium trifluoromethanesulfonylimide, 1-butyl-3-methylimidazolium di(trifluoromethanesulfonyl)imide, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium hexafluorophosphate, 3-methyl-1-hexylimidazolium bromide, and 1-ethyl-3-methylimidazolium acetate ([EMIM]Ac); The aforementioned nanofillers include at least one of nano zinc oxide, nano aluminum oxide, and nano silicon nitride; By mass percentage, the above-mentioned compound solvents comprise 60-85% of the first solvent, 10-30% of the second solvent, and 5-15% of the third solvent.

[0047] Optionally, when selecting the components of the crosslinking agent, initiator, ionic liquid, and nanofiller, if two or more components are selected for compounding, the compounding ratio is not limited here and can be compounded according to actual needs.

[0048] It should be noted that in the above crosslinking system, the methacrylate complex serves as the main chain of the network, and the difference in the length of its side chains can bring a designable glass transition temperature gradient to the network. When trifunctional crosslinking agents such as trimethylolpropane triacrylate (TMPTA) and triallyl isocyanurate (TAIC) are introduced, they can form three-dimensional star-shaped crosslinking nodes in the network, causing the network structure to evolve into a cage-like structure, which can restrict the long-range slip of chain segments. Among them, the acrylate groups of TMPTA have high copolymerization activity with the methacrylate monomers, and the reaction rates are matched. As an allyl crosslinking agent, the allyl structure of TAIC can undergo graft crosslinking with the methacrylate chain, which may form a flexible crosslinking bridge and reduce the brittleness of the network. Furthermore, polyethylene glycol diacrylate (PEGDA) and ethylene glycol dimethacrylate (EGDMA), as bifunctional crosslinking agents, can form a key complementarity with trifunctional crosslinking agents. This complementarity may manifest in the fact that TMPTA / TAIC can provide high crosslinking density and shape retention, while PEGDA / EGDMA can introduce flexible spacers between crosslinking points, allowing the network to retain necessary chain segment mobility even at ultra-high crosslinking densities. This combination of rigid nodes and flexible bridges can avoid network embrittlement that might result from using only trifunctional crosslinking, enabling the stress in the gel film to be effectively dispersed through the flexible bridges when subjected to large deformations. Dicumyl peroxide (DCP), as a peroxide, can not only initiate free radical reactions but also form macromolecular free radicals by abstracting tertiary hydrogens from the PVDF backbone and α-hydrogens from the polymethacrylate chains, thereby achieving graft crosslinking between PVDF and polymethacrylate. This grafting effect may establish a covalent bond bridge between polymers, eliminating the macroscopic phase interface and integrating the physically entangled network and the chemically crosslinked network at the molecular scale.

[0049] Initiators, the combined use of azobisisobutyronitrile (AIBN), 1,1'-azobiscyclohexanenitrile (ACHN), and benzoyl peroxide (BPO) can provide free radical release capabilities across multiple temperature windows. AIBN has a lower decomposition temperature, allowing for rapid network formation in the early stages of solvent evaporation. ACHN has a higher decomposition temperature, continuously releasing free radicals during the later high-temperature treatment phase, ensuring complete reaction deep within the high-viscosity gel. BPO, as a peroxide-based initiator, may induce a grafting effect similar to that of DCP through its decomposition products, while also synergistically expanding the temporal distribution of free radical concentration with the azo initiator. This initiation mode can match the solvent evaporation gradient from the surface to the interior, avoiding premature surface gelation and internal stress cracking caused by insufficient internal curing.

[0050] In gel film systems, ionic liquids can act as charge carriers and also function as network plasticizers, phase structure modifiers, and surfactants. Among the aforementioned ionic liquids, 1-ethyl-3-methylimidazolium trifluoromethanesulfonylimide ([EMIM]TFSI) and 1-butyl-3-methylimidazolium di(trifluoromethanesulfonyl)imide ([BMIM]TFSI) possess large volume and highly delocalized TFSI. - Anionic, hydrophobic imidazole cations may exhibit excellent affinity for the fluorinated backbone of PVDF-HFP and the ester groups of polymethacrylate. 1-Butyl-3-methylimidazolium tetrafluoroborate ([BMIM]BF4) and 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIM]PF6) have smaller anionic sizes and higher potential for ionic conductivity; among them, BF4... - It may hydrolyze to produce HF in the presence of trace amounts of moisture, while PF6- has good thermal stability; when it is compounded with TFSI-type ionic liquids, it can adjust the overall viscosity and dielectric constant of the ionic liquid and optimize the response amplitude of the double-layer capacitance.

[0051] In 3-methyl-1-hexyl imidazole bromide ([HMIM]Br), Br -Ions possess strong polarization and surface activity, enabling them to specifically adsorb onto the surface of nanofillers, forming an ion-rich interfacial layer. This enhances the electric double layer density at the electrode-gel interface, improving the initial capacitance and sensitivity of the sensor. Simultaneously, the introduction of hexyl chains increases hydrophobicity, further modulating the compatibility between the ionic liquid and the polymer matrix. The acetate ion of 1-ethyl-3-methylimidazolium acetate ([EMIM]Ac) possesses coordination ability, forming coordinate bonds with the metal centers on the nanofiller surface. This coordination improves the dispersibility of nanoparticles in the organic matrix, preventing aggregation. It also immobilizes the ionic liquid on the filler surface via chemisorption, forming a stable ion-inorganic hybrid interface. Furthermore, the low viscosity of acetate-based ionic liquids helps reduce the overall viscous resistance of the system, improving the sensor's response speed.

[0052] The aforementioned nanofillers—nano zinc oxide (ZnO), nano alumina (Al2O3), and nano silicon nitride (Si3N4)—possess large specific surface areas. The piezoelectricity of nano ZnO and PVDF may lead to electromechanical coupling, resulting in a synergistic output of charge signals under external force, which can enhance the sensor's response amplitude under dynamic loads. Simultaneously, the hydroxyl groups on the ZnO surface can form hydrogen bonds with the ester groups of polymethyl methacrylate and the anions of ionic liquids, serving as physical crosslinking points and further increasing the effective crosslinking density of the network. In the film, nano Al2O3 particles can act as rigid support points, embedded in the flexible polymer network, bearing some stress under pressure, reducing excessive slippage of the polymer chains, and thus reducing creep. The Lewis acid sites (Al2O3) on its surface... 3+ (Center) can adsorb TFSI - or PF6 - The presence of anions creates a localized ion concentration gradient around the particles. This gradient rapidly reconstructs under pressure, providing additional interfacial capacitance changes. Nano-sized Si3N4 can improve the wear resistance and dimensional stability of the film, allowing the sensor to maintain uniform thickness during repeated friction and bending cycles, thus avoiding signal drift caused by mechanical wear. Furthermore, the nitride groups that may be present on the Si3N4 surface can interact weakly with the imidazole rings, further stabilizing the distribution of ionic liquids at the interface.

[0053] In the above-mentioned compound solvent, the first solvent serves as the main solvent, while the second and third solvents serve as auxiliary solvents, which can form a volatilization gradient and further ensure the formation of the ionogel film network structure.

[0054] In one possible implementation, the first solvent comprises N,N-dimethylformamide or N,N-dimethylacetamide; the second solvent comprises N-methylpyrrolidone; and the third solvent comprises dimethyl carbonate.

[0055] It should be noted that when the first solvent includes N,N-dimethylformamide (DMF) or N,N-dimethylacetamide (DMAc), it is a uniform, strongly polar, aprotic solvent. The oxygen and nitrogen atoms of its amide groups (—CON<) can generate dipole-dipole interactions with the C-F bonds on the PVDF chain, disrupting the van der Waals forces between the PVDF molecular chains and fully dissolving the PVDF / PVDF-HFP composite. The second solvent, N-methylpyrrolidone (NMP), can act as a boiling point regulator. After coating the gel system, in the later stages of the drying process, it can prevent the PVDF chains from precipitating prematurely before they are fully relaxed and crystallized, thus avoiding stress concentration or cracks inside the film. The third solvent, dimethyl carbonate (DMC), has the lowest boiling point and evaporates the fastest compared to the first and second solvents. Within a very short time after coating, DMC can rapidly escape from the surface, allowing the wet film surface to dry quickly, thereby reducing dust adhesion and flow deformation. Furthermore, during the volatilization of DMC, the concentrations of the first and second solvents gradually increase, which can cause PVDF segments to locally aggregate and form crystal nuclei when enriched in DMC. Subsequently, when enriched in DMF / NMP, these crystal nuclei grow slowly, eventually forming nanoscale crystal regions with uniform size and regular distribution.

[0056] To achieve the above objectives, the present invention also provides a method for preparing an ion gel film with high resilience and low hysteresis properties, which is used to prepare the ion gel film as described above. Preparation methods include: S10. Dissolve the PVDF / PVDF-HFP composite in a compounding solvent and stir at room temperature until the solution is uniform and transparent; then add ionic liquid and nanofiller, sonicate, and let stand at room temperature to obtain an ionic gel-based solution. S20. Add the crosslinking system to the ion gel-based solution and stir at room temperature until homogeneous to obtain the ion gel film system; S30. Using a scraping device, based on a coating process, the ionogel film system is coated onto the surface of a backing substrate to form a wet film coating. Then, the film undergoes a first drying process and a second drying process to obtain the ionogel film attached to the surface of the backing substrate.

[0057] It should be understood that in the above preparation method, room temperature stirring refers to stirring at ambient temperature (usually 20–25°C) without additional heating or cooling.

[0058] Optionally, the duration of the above-mentioned ultrasonic treatment can be selected according to the actual situation, and can also be 5-10 minutes.

[0059] Optionally, the above coating process can be spraying, stenciling, spin coating, or scraping, etc., and can be selected according to actual needs.

[0060] Optionally, the backing substrate can be PET or PI backing substrate, and the thickness of the backing substrate can be selected according to actual needs, and can be 10um-300um.

[0061] It should be noted that in the above preparation method, the PVDF / PVDF-HFP composite is first dissolved in a compounding solvent and stirred at room temperature until it becomes uniform and transparent, which can fully dissolve the PVDF / PVDF-HFP composite. If PVDF / PVDF-HFP is directly mixed with ionic liquids, nanofillers, or other components, it will lead to severe encapsulation, meaning that the external ionic liquids and nanofillers cannot fully react with the PVDF / PVDF-HFP composite, resulting in macroscopic phase separation. Therefore, by first fully swelling and stirring the PVDF / PVDF-HFP composite in a compounding solvent, the long PVDF chains can gradually extend, and the HFP units of PVDF-HFP loosen due to solvation, achieving a molecular-level uniform dispersion of the entire system.

[0062] After the polymer is completely dissolved, ionic liquid and nanofiller are added, and ultrasonic treatment is used to disperse the filler through mechanical effect. Local high temperature and high pressure micro-regions are generated through cavitation effect, which desorbs the physically adsorbed gas on the surface of nanoparticles and promotes the wetting of ionic liquid on the surface of nanoparticles, forming ionic liquid-coated nano-hybrid particles.

[0063] Finally, the crosslinking system is added and thoroughly mixed under stirring at room temperature. At this point, the initiator decomposes at a low rate at room temperature, thus maintaining chemical stability, while the methacrylate monomer can penetrate into the nanopores between the PVDF chains.

[0064] In one possible implementation, the steps of sequentially performing the first drying process and the second drying process include: After the ionogel film system is coated on the surface of the backing substrate, it is placed in a drying equipment and dried at 70-85℃ for 3-24h; then it is vacuum dried at 70-80℃ for 48-72h.

[0065] In one possible implementation, the thickness of the wet film coating is 100-2000 μm.

[0066] It should be noted that during the first drying process described above, at 70-85℃, residual initiators such as AIBN and BPO begin to decompose, generating free radicals, which causes the methacrylate monomers and crosslinking agents to undergo in-situ polymerization. DMC fully volatilizes, while DMF begins to volatilize slowly. Furthermore, the drying time at this temperature can be selected based on the thickness of the wet film coating. For example, if the wet film coating thickness is <100μm, the drying time can be controlled at 3-6 hours; if it is >200μm, the time can be extended to 24 hours to ensure sufficient solvent evaporation. As DMC and some DMF are removed, the solution concentration increases, and the entangled network of PVDF segments gradually shrinks from the swollen state to the dry state. If the chemical crosslinking reaction proceeds simultaneously, the polymethacrylate network grows and crosslinks in situ within the gaps of the PVDF physical network; simultaneously, the crystallization of PVDF is further perfected at this temperature.

[0067] After the first drying process, a second drying process is performed. The system pressure is significantly reduced under vacuum, and the boiling point of the solvent also decreases. Therefore, at a temperature of 70-80℃, the residual solvent migrates from the interior of the film to the surface and escapes, evaporating completely. After the drying process, the chemical cross-linking network in the film can form a dense three-dimensional cage structure. Some residual solvent molecules may be physically adsorbed into the network pores, making rapid evaporation difficult. For sensor applications, residual solvent can interfere with the electric double layer structure of the ionic liquid, causing capacitance baseline drift; or it can slowly seep out, corroding the electrode interface and causing the film swelling degree to change over time. Therefore, the second drying process requires 48-72 hours of vacuum drying to ensure that the residual solvent is reduced to the ppb level.

[0068] To achieve the above objectives, the present invention also provides an ionized thin-film pressure sensor comprising the ion gel thin film as described above.

[0069] Optionally, the assembly method of the above-mentioned ion gel film in the ionized thin film pressure sensor can be selected according to actual needs. Alternatively, the ion gel film attached to the surface of the backing substrate can be assembled face-to-face with the interdigitated electrodes to form an AB structure sensor using an annular double-sided adhesive tape, and the outer layer of the backing is encapsulated and protected with PI tape.

[0070] In ionized thin-film pressure sensors, electrical signal delay can be caused by factors such as ion migration relaxation in the gel phase, hysteresis in the mechanical response of polymer segments to external forces, and charging / discharging delay of the double layer at the electrode / gel interface. When the sensor contains the aforementioned ion-gel thin film, in terms of ion transport, ions can quickly rearrange under pressure, significantly shortening the build-up time of the double-layer capacitance. Simultaneously, the molecular weight distribution characteristics of PVDF-HFP ensure a short relaxation time for chain segment movement, avoiding the problem of delayed chain segment response time in wide-distribution systems. When external forces are applied to the film, the amorphous regions of PVDF-HFP can respond quickly, causing the ionic liquid to migrate to the interface. Furthermore, the physical entanglement network formed by the molecular properties of PVDF provides instantaneous elastic support. When the moduli of both are matched, the conversion from mechanical to electrical signals occurs almost simultaneously, thus solving the problems of electrical signal delay, decreased accuracy, and deteriorated system stability.

[0071] Example 1 An ionogel film, comprising, by mass parts, 10 parts of PVDF / PVDF-HFP composite, 8 parts of cross-linking system, 5 parts of ionic liquid, 1.0 part of nanofiller and 76 parts of composite solvent; In the PVDF / PVDF-HFP compound, the weight-average molecular weight of PVDF is 900,000-950,000 g / mol, with a molecular weight distribution of 2.5-3.0; the weight-average molecular weight of PVDF-HFP is 400,000-450,000 g / mol, with a molecular weight distribution of 1.5-2.0; by mass percentage, PVDF accounts for 60% and PVDF-HFP accounts for 40%. By mass percentage, the crosslinking system consists of 65% methacrylate compound, 25% crosslinking agent, and 10% initiator; the methacrylate compound is composed of MMA and n-BMA in a mass ratio of 3:2; the crosslinking agent is composed of TMPTA and EGDMA in a mass ratio of 3:1; and the initiator is composed of AIBN and BPO in a mass ratio of 3:1. The ionic liquid is composed of [EMIM]TFSI and [BMIM]BF4 in a mass ratio of 2:1; the nanofiller is composed of nano Al2O3 and ZnO in a mass ratio of 3:2; the compounding solvent is composed of the first solvent DMF, the second solvent NMP, and the third solvent DMC in a mass percentage of 60%, 30%, and 10%, respectively. The preparation method of ionogel films with high resilience and low hysteresis is as follows: S10. Dissolve the PVDF / PVDF-HFP composite in a compounding solvent and stir at room temperature until the solution is uniform and transparent; then add ionic liquid and nanofiller, sonicate for 5 min, and let stand at room temperature to obtain an ionic gel-based solution; S20. Add the crosslinking system to the ion gel-based solution of S10, and stir at room temperature until homogeneous to obtain the ion gel film system; S30. Using a blade coater, the S20 ionogel film system is coated onto the surface of a PI backing substrate to form a wet film coating with a thickness of approximately 200 μm. The coated film is then placed in an 80°C oven and dried under normal pressure for 12 hours. During this stage, DMC rapidly volatilizes, DMF is gradually removed, and AIBN and BPO decompose. Methacrylate polymerizes in situ, forming a chemical cross-linked network that interpenetrates with the PVDF physical network. The crystallization of PVDF is further perfected at this temperature, forming nanoscale crystalline regions. The film was transferred to a vacuum drying equipment and dried at 75°C and a vacuum degree ≤100Pa for 48 hours. During this stage, the vacuum was used to lower the boiling point of the high-boiling solvent, achieving deep removal to a residual amount as low as ppb, while eliminating network internal stress and improving interface bonding. After drying, an ionogel film is obtained that adheres to the surface of the PI backing substrate.

[0072] The ion gel film obtained by S10-S30 and attached to the surface of the PI backing substrate is assembled face-to-face with the interdigitated electrodes to form an AB structure sensor, which is then encapsulated and protected with PI tape. This sensor is then applied to an ionized thin-film pressure sensor to obtain an ionized thin-film pressure sensor including the ion gel film.

[0073] A schematic diagram of the structure of an ionized thin-film pressure sensor is shown below. Figure 1 As shown, the left figure is a top view of the planar helical interdigitated electrode, and the right figure is a schematic diagram of the sensor cross-sectional structure.

[0074] As shown in the left figure, the spiral coils outward from the center, with uniform line width and spacing. A straight lead extends from both the left and right sides, connecting to the external circuitry. In this ion-type sensor, the spiral interdigitated electrode serves as the lower electrode. An ion-gel film with a backing is assembled face-to-face with the interdigitated electrode to form the sensor. When the ion-gel is compressed, it is squeezed into the spiral gap, increasing the effective edge length of the electrode and significantly amplifying the change in double-layer capacitance. As shown in the right figure, the uppermost layer represents the upper flexible encapsulation layer or protective layer, covering the entire sensitive area. The middle layer represents the ion-gel film, and the lower layer represents the patterned interdigitated electrode of the lower electrode. Under pressure, the film deforms and indents into the gap, creating a localized large strain zone, significantly enhancing the rearrangement rate of ions at the interface and improving sensitivity.

[0075] The ionogel film obtained in Example 1 was characterized by FTIR, and the results are as follows: Figure 2 As shown.

[0076] like Figure 2The black curve represents the diffraction peak of the PVDF homopolymer, the red curve represents the diffraction peak of the PVDF-HFP copolymer, and the blue curve represents the diffraction peak of the ionogel film; in the figure, 836 cm⁻¹ -1 The peak can be attributed to the CF stretching and CH2 out-of-plane rocking coupling vibrations of the PVDF β phase. The β phase is the piezoelectrically active polar crystalline phase of PVDF, and the presence of this peak indicates that PVDF contains a certain proportion of the β phase, confirming that PVDF of a specific molecular weight can provide a piezoelectric framework. (1070 cm⁻¹) -1 The nearby broad peak represents the CF2 stretching vibration region; 1180cm -1 With 1210cm -1 This can be attributed to the bimodal stretching vibration of CF, a characteristic of the PVDF skeleton; 1400cm -1 This can be classified as an in-plane torsional vibration of CH2; 1650-1750cm -1 The absence of significant absorption in the 1228 cm⁻¹ region indicates that PVDF does not contain polar functional groups such as carbonyl groups. Compared to PVDF, the introduction of HFP units brings about structural changes, with a 1228 cm⁻¹ region... -1 With 1349cm -1 These two peaks are significantly enhanced and sharpened in PVDF-HFP. The HFP structure contains -CF3 side groups and CF bonds, and this peak belongs to the CF stretching vibration mode, including symmetric and asymmetric stretching of -CF3. This is a distinctive feature of PVDF-HFP compared to PVDF. (836 cm⁻¹) -1 Near the PVDF, the intensity of the characteristic peak of the β phase is significantly lower than that of PVDF. This may be because the introduction of HFP disrupts chain regularity, inhibits the full crystallization of the β phase, and increases the proportion of amorphous regions. This is consistent with the previously discussed PVDF-HFP as an amorphous ion storage interstitial structure. The blue curve shows that at 836 cm⁻¹... -1 1228cm -1 1311cm -1 1349cm -1 All absorption peaks were clearly observed, indicating that the chemical structures of PVDF and PVDF-HFP remained intact in the disclosed preparation method, without significant chemical degradation or HF removal reactions; furthermore, an absorption peak at 1725 cm⁻¹ was observed. -1 The strong peak, attributed to the stretching vibration of the carbonyl group (C=O) in the methacrylate polymer, confirms the successful introduction and polymerization of the methacrylate crosslinking network into the gel film; however, it differs from the 1730 cm⁻¹ peak of pure PMMA. -1 The slightly weaker transmittance compared to PVDF and PVDF-HFP may be due to the dipole interaction between the ester carbonyl group and the ionic liquid and the CF group of PVDF, resulting in a slight red shift. The overall transmittance of the blue curve differs slightly from that of PVDF and PVDF-HFP, which may be due to the absorption effect of the ionic liquid, leading to an increase in background absorption.

[0077] Through the Figure 2 Analysis shows that the intrinsic piezoelectricity of PVDF is retained in the ionogel film, which can synergize with the ionization effect to achieve dual-modal sensing; the physical entanglement network of ultra-high molecular weight PVDF restores its crystalline structure after reforming; PVDF-HFP is uniformly dispersed in the gel film and has a complete chemical structure, with a thickness of 1228 cm⁻¹. -1 and 1349cm -1 The amorphous region corresponding to the peak is the main enrichment region of the ionic liquid; 1725 cm⁻¹ -1 The peak intensity and half-peak width can reflect the degree of polymerization of the cross-linked network. The peak is sharp and of moderate intensity, which proves that the methacrylate monomer has been fully polymerized. The spectrum does not show obvious peak splitting or abnormal broadening, indicating that no macroscopic phase separation has occurred between PVDF, PVDF-HFP, polymethacrylate and ionic liquid.

[0078] The ionogel film obtained in Example 1 was measured by SEM, and the results are as follows: Figure 3 As shown.

[0079] like Figure 3 The left image, magnified 500 times, shows the macroscopic morphology, while the right image, magnified 2000 times, shows the microscopic morphology. The left image shows a uniformly distributed sponge-like porous structure on the film surface, with pore sizes mainly concentrated in the 5-15 μm range. The pore walls are thin and interconnected, forming a continuous three-dimensional skeletal network. The pore distribution shows no obvious orientation, indicating that the phase separation process is controlled and isotropic, and the shear stress during coating did not cause the pores to oriented. The right image, magnified 2000 times, shows that the pore wall surface is covered with nanoscale granular or spherical protrusions, approximately 100-300 μm in size. These nanoscale protrusions are densely arranged, forming the secondary structure of the pore walls. The pore edges exhibit irregular polygonal or elliptical shapes, and local wrinkles are visible in some areas, indicating that the film has a certain degree of flexibility and undergoes reversible elastic deformation during drying and shrinkage.

[0080] pass Figure 3Analysis reveals that the hierarchical porous structure is the result of the combined effects of solvent evaporation-induced phase separation and in-situ polymerization network. During the initial drying stage after coating, the third solvent, DMC, causes a local increase in polymer concentration. Since DMC has a weak dissolving capacity for PVDF, its rapid removal promotes the precipitation of PVDF segments from the solution, forming nanoscale nuclei. These nuclei act as primary aggregation centers, attracting surrounding PVDF-HFP and unpolymerized methacrylate monomers to aggregate, forming a polymer-rich phase. As DMF and NMP are gradually removed, the solvent-rich phase eventually shrinks into pores, and the polymer-rich phase solidifies into pore walls. The nanoscale protrusions on the pore wall surface in the figure may represent the morphology of nanoparticles exposed on the surface after being encapsulated by polymer chains, or the appearance of PVDF nanocrystal regions growing using filler as a template. The presence of these nanostructures prevents excessive shrinkage and collapse of the pore walls during the drying process.

[0081] The hierarchical porous structure can further increase the specific surface area of ​​the thin film. In ion-type sensors, the double-layer capacitance is proportional to the effective area of ​​the electrode-electrolyte interface. When the ion gel film is sandwiched between spiral electrodes, the inner walls of the pores can provide more charge storage surface. The distribution of ionic liquid in the channels can significantly improve the effective interfacial capacitance density. This structural characteristic can be translated into high sensor sensitivity. Under slight pressure, the pore walls will also undergo slight deformation, resulting in significant changes in the ion distribution within the channels and a significant response of the interfacial capacitance. In addition, the connectivity of the pores can provide a low-torsion transport path for ions, effectively improving ionic conductivity. This also proves that the fast response channel of PVDF-HFP with defined molecular characteristics can enable the sensor to achieve millisecond-level response time. The hierarchical porous interconnected structure has structural elasticity. Under pressure, the pore walls bend and deform, storing elastic energy; after the pressure is removed, the pore walls rebound, and the pores return to their original size. In conjunction with the three-dimensional skeleton network structure, it can further enhance the low hysteresis and high resilience characteristics of the thin film.

[0082] The dynamic response characteristics of the ionized thin-film pressure sensor obtained in Example 1 were measured, and the results are as follows: Figure 4 As shown.

[0083] like Figure 4 It exhibits three complete load-unload cycles, each containing multiple stepped plateaus, with the capacitance jumping from the baseline along a substantially vertical edge to approximately 4.0 × 10⁻⁶. -8The pressure rises to 40 nF, followed by 2-3 secondary steps within the high-pressure platform, before finally falling back down. This step-like rather than sloping upward curve indicates that the sensor can distinguish graded pressures. As the external pressure gradually increases in a stepwise manner, the multi-level network structure of the ion gel film undergoes progressive deformation. Under low pressure, the micron-sized pores on the film surface first undergo elastic compression, squeezing the ionic liquid into the gaps between the pore walls, and the double-layer capacitance rises rapidly. Under medium pressure, the amorphous soft sea area of ​​PVDF-HFP becomes further densified, the ion channels narrow, and the interface density increases. Under high pressure, the nano-hard island regions of PVDF begin to participate in load-bearing, the piezoelectric effect is superimposed on the ionization effect, and the capacitance enters a saturation platform. Each step corresponds to a stable mechanical-electrical equilibrium state, indicating that the sensor can quickly reach a steady state under each pressure level without continuous creep. In addition, the rising and falling edges of the capacitance show a basically vertical trend, indicating that the response time and recovery time are both in the order of seconds or even sub-seconds. The waveforms of the three cycles highly overlapped, with the baseline, peak value, step height, and plateau duration being almost identical. This indicates that the mechanical rebound is completely reversible. This is due to the synergistic effect of the entropy elasticity of the physical entanglement network of PVDF with defined molecular properties and the shape of the high-density chemical cross-linked network of methacrylate, which prevents permanent deformation accumulation in the film during repeated compression and rebound. There was no leakage of the ionic liquid because the chemically cross-linked microcages and PVDF crystalline barriers fixed the ionic liquid in the nanopores, and the total ion amount remained constant throughout the three cycles, with no drift in the capacitance baseline. There was no interface degradation, indicating that the nanofiller and the ionic liquid layer remained stable at the electrode and gel interface, without peeling or electrochemical corrosion due to repeated deformation.

[0084] The long-term stability of the ionized thin-film pressure sensor obtained in Example 1 was tested, and the results are as follows: Figure 5 As shown.

[0085] like Figure 5 The results show the sensor's long-term stability and baseline drift over 24 hours, covering approximately 24-36 hours of continuous monitoring, with the capacitance value generally maintained at 4.0 × 10⁻⁶. -8 The high region near F (40nF) shows a relatively stable red band with slight sawtooth fluctuations at the top. Over long timescales, the capacitance did not exhibit significant upward or downward drift, indicating that there is virtually no solvent residue in the gel film, and the two-stage drying process in the preparation method effectively removes residual solvent. The ionic liquid remains stable within the structural pores and does not migrate. The slight sawtooth fluctuations at the top may be due to factors such as ambient temperature and noise from the testing system.

[0086] Example 2

[0087] In the preparation method, the drying process is as follows: place it in a drying device and dry it at 85°C for 6 hours; then use a vacuum drying device to vacuum dry it at 80°C for 55 hours; the remaining technical features are consistent with those of Example 1.

[0088] Example 3

[0089] In the preparation method, the drying process is as follows: the sample is placed in a drying device and dried at 80°C for 10 hours; then, it is vacuum dried at 75°C for 65 hours using a vacuum drying device. All other technical features are consistent with those of Example 1.

[0090] Example 4

[0091] All other technical features are consistent with those in Example 1.

[0092] Example 5

[0093] All other technical features are consistent with those in Example 1.

[0094] The hysteresis and full-scale drift performance of the ion-gel thin-film pressure sensor containing the ion-gel thin film obtained in Examples 1-5 were tested using the following method.

[0095] Hysteresis Test Method: The pressure source equipment is pressurized in a stepped pressurization mode: 0 MPa, 0.2 MPa, 0.4 MPa, 0.6 MPa, 0.8 MPa, 1 MPa, 1 MPa, 0.8 MPa, 0.6 MPa, 0.4 MPa, 0.2 MPa, 0 MPa. Each step lasts 30 seconds, constituting one cycle. Three cycles are required. Force and electrical signal data are collected during this test. Within the specified range, at the same test point, the value is calculated using the absolute value of the difference between the output and the increase / decrease of the measured value.

[0096] Full-scale dynamic drift test method: The pressure source device is pressurized. The test mode starts from zero pressure, applies continuous force until the expected range is reached, and then continuously reduces the pressure from the expected range back to zero pressure. This process constitutes one cycle, with a cycle period of 40 seconds. 1000 cycles are required for the test. Force data and electrical signal data are collected during the test. The percentage of the maximum difference in full-scale output value to the initial full-scale output value is calculated over the entire test cycle.

[0097] The test results are shown in Table 1. Table 1

[0098] Analysis of the test data in Table 1 shows that the hysteresis of the ion-gel films obtained in Examples 1-5 can be controlled within 5%, meaning that the maximum deviation between the loading and unloading curves within the full-scale output is within 5% of the total range. The full-scale drift after 1000 cycles can be controlled within 6%, meaning that after 1000 full-scale cycles, the change in the initial or full-scale output relative to the original value is within 6% of the full-scale range.

[0099] Comparative Example 1 Comparative Example 1 was set up under Example 1. In Comparative Example 1, the PVDF / PVDF-HFP complex in Example 1 was replaced with a PVDF complex with a crystallinity of about 50% and a PVDF-HFP complex with a crystallinity of about 10%. All other technical features were the same as those in Example 1.

[0100] Comparative Example 2 Comparative Example 2 was set up under Example 1. In Comparative Example 2, the PVDF / PVDF-HFP complex in Example 1 was replaced with a pure PVDF system that did not contain PVDF-HFP; all other technical features were the same as those in Example 1.

[0101] Comparative Example 3 Comparative Example 3 was set up under Example 1, in which the methacrylate complex was removed; all other technical features were the same as those in Example 1.

[0102] Comparative Example 4 Comparative Example 4 was set up under Example 1, in which the compound solvent was replaced by a single solvent DMF; all other technical features were the same as those in Example 1.

[0103] The hysteresis and drift of sensors containing gel films of Comparative Examples 1-4 were measured using the same test method as in the Examples, and the results are shown in Table 2.

[0104] Table 2

[0105] In Comparative Example 1, the PVDF / PVDF-HFP composite was replaced with a PVDF composite with approximately 50% crystallinity and a PVDF-HFP composite with approximately 10% crystallinity. The PVDF with approximately 50% crystallinity can form rigid crystalline regions that are difficult to deform under pressure. The PVDF-HFP with approximately 10% crystallinity forms a highly viscoelastic soft gel phase after swelling the ionic liquid. When pressure is applied, the soft phase is compressed, and ions migrate to the electrode interface. When the pressure is released, the soft phase rebounds slowly, and shear slip occurs at the interface between the hard phase and the soft phase, making it difficult to recover synchronously. This asynchronous mechanical deformation problem manifests as a lag in the electrical signal. Furthermore, PVDF with a crystallinity of approximately 50% indicates that it contains a large number of layered wafer structures. During 1000 cycles of compression, the wafers may fracture, slip, or rearrange their orientation at stress concentration points. This manifests as a gradual decrease in the material's equivalent modulus and a gradual increase in deformation under the same pressure, resulting in a significant drift in full-scale output. On the other hand, PVDF-HFP with a crystallinity of approximately 10% indicates that it contains approximately 90% amorphous regions, which will swell with a large amount of ionic liquid. Under cyclic compression, the amorphous segments will undergo irreversible slippage and rearrangement, and the film will undergo permanent compression deformation. In sensors, this manifests as a significant drift in the thickness baseline, leading to a significant drift in full-scale output.

[0106] In Comparative Example 2, the use of a pure PVDF system results in a lack of amorphous ion storage gaps in the gel film. Ionic liquids can only be adsorbed on the surface of the PVDF crystal region and a small number of amorphous gaps, which significantly reduces the effective ion channels and increases their tortuosity. At the same time, the rigid framework of PVDF leads to an excessively high film modulus, making deformation difficult under low pressure and significantly reducing sensitivity. During cycling, ionic liquids may gradually desorb and migrate from the surface of the crystal region, which will ultimately exacerbate the hysteresis and drift problems of the sensor.

[0107] In Comparative Example 3, the absence of methacrylate in the system leads to a significant enhancement of the plasticizing effect of the ionic liquid on PVDF-HFP during cross-linking, resulting in irreversible slippage of the polymer chains. This causes the film to be unable to rebound after being compressed, and the ionic liquid undergoes macroscopic migration and leakage under stress, ultimately leading to a continuous drift of the sensor's capacitance baseline and a severe hysteresis problem.

[0108] Comparative Example 4 uses a single solvent, which accelerates the dissolution rate. After coating and drying, the pure DMF has a single evaporation rate, and the film surface will quickly form a skin, creating a dense hard shell. This prevents the solvent inside the film from escaping, causing stress concentration and cracking inside the film. This significantly reduces the effective double layer area, ultimately leading to film performance degradation and prominent problems such as hysteresis and drift in the sensor.

[0109] The above are merely preferred embodiments of the present invention and do not limit the scope of the patent. Any equivalent structural or procedural transformations made based on the description and drawings of the present invention, or direct or indirect applications in other related technical fields, are similarly included within the scope of patent protection of the present invention.

Claims

1. An ionogel film, characterized in that, The ion gel film includes a three-dimensional framework network structure and a multi-level porous interconnected structure. The ion gel film system includes a PVDF / PVDF-HFP composite; In the PVDF / PVDF-HFP compound, the weight-average molecular weight of PVDF is 900,000-1,100,000 g / mol, and the molecular weight distribution is 2.5-3.0; the weight-average molecular weight of PVDF-HFP is 400,000-600,000 g / mol, and the molecular weight distribution is 1.5-2.

0.

2. The ionogel film according to claim 1, characterized in that, The ionogel film system further includes a crosslinking system; by mass parts, the crosslinking system accounts for 5-15 parts of the ionogel film system. The crosslinking system comprises, by mass percentage, 60-83% methacrylate compound, 15-30% crosslinking agent, and 5-10% initiator; The methacrylate compound is composed of at least two of the following: methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, and isobutyl methacrylate. The PVDF / PVDF-HFP composite accounts for 5-20 parts by weight of the ionogel film system; In PVDF / PVDF-HFP blends, by mass percentage, PVDF is 60-95% and PVDF-HFP is 5-40%.

3. The ionogel film according to claim 1, characterized in that, The ion gel film system further comprises 3-10 parts by mass of ionic liquid, 0.1-2.0 parts by mass of nanofiller, and 60-85 parts by mass of compound solvent.

4. The ionogel film according to claim 2, characterized in that, The crosslinking agent includes at least one of trimethylolpropane triacrylate, triallyl isocyanurate, polyethylene glycol diacrylate, ethylene glycol dimethacrylate, and dicumyl peroxide; The initiator includes at least one of azobisisobutyronitrile, 1,1'-azobiscyclohexanenitrile, and benzoyl peroxide.

5. The ionogel film according to claim 3, characterized in that, The ionic liquid comprises at least one of the following: 1-ethyl-3-methylimidazolium trifluoromethanesulfonylimide, 1-butyl-3-methylimidazolium di(trifluoromethanesulfonyl)imide, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium hexafluorophosphate, 3-methyl-1-hexylimidazolium bromide, and 1-ethyl-3-methylimidazolium acetate. The nanofiller includes at least one of nano zinc oxide, nano aluminum oxide and nano silicon nitride; The compounded solvent comprises, by mass percentage, 60-85% of a first solvent, 10-30% of a second solvent, and 5-15% of a third solvent.

6. The ionogel film according to claim 5, characterized in that, The first solvent includes N,N-dimethylformamide or N,N-dimethylacetamide; the second solvent includes N-methylpyrrolidone; and the third solvent includes dimethyl carbonate.

7. A method for preparing an ionogel film, characterized in that, The preparation method is used to prepare the ion gel film as described in any one of claims 1-6; The preparation method includes: The PVDF / PVDF-HFP composite was dissolved in a compounding solvent and stirred at room temperature until the solution was uniform and transparent. Then, ionic liquid and nanofiller were added sequentially, and after ultrasonic treatment, the solution was allowed to stand at room temperature to obtain an ion gel-based solution. A crosslinking system was added to the ion gel-based solution and stirred at room temperature until homogeneous to obtain the ion gel film system. Using a coating equipment and based on a coating process, the ionogel film system is coated onto the surface of a backing substrate to form a wet film coating. Then, the film undergoes a first drying process and a second drying process to obtain the ionogel film attached to the surface of the backing substrate.

8. The preparation method according to claim 7, characterized in that, The steps involving the first drying process and the second drying process in sequence include: After the ionogel film system is coated on the surface of the backing substrate, it is placed in a drying equipment and dried at 70-85℃ for 3-24 hours; then it is vacuum dried at 70-80℃ for 48-72 hours using a vacuum drying equipment.

9. The preparation method according to claim 7, characterized in that, The thickness of the wet film coating is 100-2000 μm.

10. An ionized thin-film pressure sensor, characterized in that, The ionized thin-film pressure sensor includes the ion gel thin film as described in any one of claims 1-6.